Design of Sustainable Biomaterial Composite Adsorbents for Point-of-Use Removal of Lead Ions From Water - Mohamed, Mohamed H.; Udoetok, Inimfon A.; Solgi, Mostafa; Steiger, Bernd G. K.; Zhou, Zexian; Wilson, Lee D. (Frontiers in Water, 2022)
The uncontrolled release of contaminants into aquatic environments has created the need for improved adsorbent materials for point-of-use (POU) treatment applications to address water security. The goal of this study was to prepare a low-cost sustainable adsorbent material with tailored Pb(II) adsorption properties in aqueous media. Several types of ternary composite adsorbents were prepared that contain chitosan, kaolinite, and a biomass additive (oat hulls or torrefied wheat straw), along with spectral characterization and thermal analysis of the adsorbents. The adsorption properties of the ternary composites with lead nitrate were studied at equilibrium using batch mode and dynamic conditions with a fixed bed column under variable experimental conditions (flow rate, bed height, and Pb(II) concentration). The adsorption capacity at equilibrium in synthetic or tap water was found to depend on the relative composition (wt.%) of additive components of the composite. The optimal composite adsorbent for maximum Pb(II) removal was determined, as follows: chitosan (50%) + kaolinite (10%) + oat hulls (40%). Using this adsorbent, the dynamic adsorption properties with lead nitrate were studied in a fixed bed column at pH 6.5 and 295 K to reveal optimized Pb(II) removal that concur with results obtained from batch studies. The sustainability of the biocomposite adsorbent was demonstrated with the use of relatively low-cost and locally available materials, whilst achieving favourable Pb(II) adsorption properties. The facile preparation of the optimal biocomposite adsorbent herein is proposed for use as a disposable POU filter media technology for the removal of lead and other multivalent heavy metal cations, including organic contaminants such as cationic dyes and agrochemicals.